CN103242551A - Method for injecting titanium ions to modify surface of polyether-ether-ketone - Google Patents
Method for injecting titanium ions to modify surface of polyether-ether-ketone Download PDFInfo
- Publication number
- CN103242551A CN103242551A CN2013101882599A CN201310188259A CN103242551A CN 103242551 A CN103242551 A CN 103242551A CN 2013101882599 A CN2013101882599 A CN 2013101882599A CN 201310188259 A CN201310188259 A CN 201310188259A CN 103242551 A CN103242551 A CN 103242551A
- Authority
- CN
- China
- Prior art keywords
- ketone
- carbon fiber
- ether
- polyether ether
- ether ketone
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Granted
Links
Images
Landscapes
- Materials For Medical Uses (AREA)
Abstract
本发明涉及一种注入钛离子对聚醚醚酮表面进行改性的方法,所述方法使用等离子体浸没离子注入技术在聚醚醚酮的表面进行钛离子注入。通过本发明改性处理得到的聚醚醚酮材料,其表面可获得不同的纳米结构,生物相容性得到显著提高;并具有潜在的骨诱导生长因子和抗菌药物装载前景。
The invention relates to a method for modifying the surface of polyether ether ketone by implanting titanium ions. The method uses plasma immersion ion implantation technology to implant titanium ions on the surface of polyetherether ketone. The surface of the polyether ether ketone material obtained through the modification treatment of the invention can obtain different nanostructures, and the biocompatibility is significantly improved; and it has potential loading prospects of osteoinductive growth factors and antibacterial drugs.
Description
技术领域 technical field
本发明涉及一种对医用聚醚醚酮表面进行改性的方法,具体说,是涉及一种使用等离子体浸没离子注入技术对聚醚醚酮及其衍生复合材料表面进行改性的方法,属于医用高分子材料表面改性技术领域。 The present invention relates to a method for modifying the surface of medical polyether ether ketone, in particular to a method for modifying the surface of polyether ether ketone and its derived composite materials by using plasma immersion ion implantation technology, belonging to The technical field of surface modification of medical polymer materials. the
背景技术 Background technique
近年来,随着生物材料制备使用理论和技术的不断完善和发展,高分子植入体材料的应用前景将更为广阔。聚醚醚酮(PEEK)的弹性模量与人体骨组织最为匹配,可有效减少应力遮挡效应造成的骨吸收和骨萎缩,且抗疲劳性突出,适合用于医疗植入装置长期植入(Biomaterials 2007,28:4845-4869)。然而,PEEK的生物活性较差,植入人体后不易与人体骨组织键合,限制了其作为植入体材料长期植入。如何提高PEEK材料生物相容性已经成为研究热点之一。 In recent years, with the continuous improvement and development of the theory and technology for the preparation and use of biological materials, the application prospects of polymer implant materials will be broader. The elastic modulus of polyetheretherketone (PEEK) best matches that of human bone tissue, which can effectively reduce bone resorption and bone atrophy caused by the stress shielding effect, and has outstanding fatigue resistance, making it suitable for long-term implantation of medical implants (Biomaterials 2007, 28:4845-4869). However, the biological activity of PEEK is poor, and it is not easy to bond with human bone tissue after implantation in the human body, which limits its long-term implantation as an implant material. How to improve the biocompatibility of PEEK materials has become one of the research hotspots. the
目前对聚醚醚酮材料进行表面改性的主要方法是化学接枝法,这种方法改性深度浅,效果较差,且反应时间长,效率低,不利于大规模生产。 At present, the main method for surface modification of polyetheretherketone materials is the chemical grafting method. This method has a shallow modification depth, poor effect, long reaction time and low efficiency, which is not conducive to large-scale production. the
发明内容 Contents of the invention
本发明为解决现有的医用聚醚醚酮存在生物相容性不佳的问题,提供一种新颖的医用聚醚醚酮材料的表面改性方法,以满足医用聚醚醚酮材料所需的生物相容性需求。 In order to solve the problem of poor biocompatibility of the existing medical polyether ether ketone, the present invention provides a novel surface modification method of medical polyether ether ketone materials, so as to meet the requirements of medical polyether ether ketone materials. biocompatibility requirements. the
等离子体浸没离子注入技术(Plasma immersion ion implantation,PIII)是一种具有全方位及高反应活性特点的新型表面改性技术,具有全方位和高反应活性的特点,对于处理体积小且异型的植入体材料具有独特的优势。使用PIII技术对绝缘体材料进行改性时,由于绝缘体导电性差而易导致表面电荷积累,影响材料改性效果,甚至毁坏材料(Surface & Coatings Technology,2005,196:162-166.)。如何应用PIII技术对高分子材料表面实现有效的表面成分以及表面结构调控成为一个难题,尤其是在对材料表面结构制备方面,仍未有相关理论和实验研究。 Plasma immersion ion implantation (PIII) is a new surface modification technology with all-round and high reactivity characteristics. It has the characteristics of all-round and high reactivity. In-body materials have unique advantages. When using PIII technology to modify insulator materials, the poor conductivity of insulators can easily lead to surface charge accumulation, affecting the effect of material modification, and even destroying materials (Surface & Coatings Technology, 2005, 196: 162-166.). How to apply PIII technology to achieve effective surface composition and surface structure regulation on the surface of polymer materials has become a difficult problem, especially in the preparation of material surface structures, there is still no relevant theoretical and experimental research. the
钛(Ti)作为硬组织植入体的传统首选材料,已被广泛证实具有良好的生物相容性,钛及其合金材料植入人体后可与人体组织有效结合;同时,氧化钛纳米颗粒具有一定抗菌性,可有效抑制细菌在植入体表面形成菌膜。有研究表明纳米尺度材料对唤起适当细胞反应,调节细胞在材料表面的粘附和分化,促进骨再生,改善并延长植入体使用效果和寿命具有重要作用,所以,纳米生物材料及生物材料表面纳米化已成为生物医用材料领域的研究热点 (Materials Science&Engineering R-Reports,2010,70:275-302.)。本申请提出通过采用等离子体浸没离子注入技术对聚醚醚酮材料进行Ti离子注入改性,在材料表面引入钛元素,同时在材料表面形成具有纳米结构的原位改性层,赋予材料一定的抗菌性,保持材料力学稳定性的同时大幅提高其生物相容性。 Titanium (Ti), as the traditional material of choice for hard tissue implants, has been widely proven to have good biocompatibility. Titanium and its alloy materials can be effectively combined with human tissues after implantation in the human body; at the same time, titanium oxide nanoparticles have Certain antibacterial properties can effectively inhibit bacteria from forming a biofilm on the surface of the implant. Studies have shown that nanoscale materials play an important role in evoking appropriate cell responses, regulating cell adhesion and differentiation on the surface of materials, promoting bone regeneration, and improving and prolonging the use and life of implants. Therefore, nanobiological materials and biomaterial surfaces Nanoization has become a research hotspot in the field of biomedical materials (Materials Science & Engineering R-Reports, 2010, 70:275-302.). This application proposes to use plasma immersion ion implantation technology to carry out Ti ion implantation modification on polyetheretherketone material, introduce titanium element on the surface of the material, and at the same time form an in-situ modification layer with nanostructure on the surface of the material, endowing the material with a certain Antibacterial property, while maintaining the mechanical stability of the material, it greatly improves its biocompatibility. the
在此,本发明提供一种注入钛离子对聚醚醚酮表面进行改性的方法,所述方法使用等离子体浸没离子注入技术在聚醚醚酮的表面进行钛离子注入。 Herein, the present invention provides a method for modifying the surface of polyether ether ketone by implanting titanium ions. The method uses plasma immersion ion implantation technology to perform titanium ion implantation on the surface of polyether ether ketone. the
通过本发明改性处理得到的聚醚醚酮材料,其表面可获得不同的纳米结构,生物相容性得到显著提高;并具有潜在的骨诱导生长因子和抗菌药物装载前景。细胞增殖实验证实,经过本发明改性处理得到的碳纤维增强聚醚醚酮材料表面MC3T3成骨细胞增殖明显高于未改性样,可满足医用碳纤维增强聚醚醚酮所需的性能要求。 The surface of the polyether ether ketone material obtained through the modification treatment of the invention can obtain different nanostructures, and the biocompatibility is significantly improved; and it has potential loading prospects of osteoinductive growth factors and antibacterial drugs. The cell proliferation experiment proves that the proliferation of MC3T3 osteoblasts on the surface of the modified carbon fiber reinforced PEEK material obtained by the present invention is significantly higher than that of the unmodified sample, which can meet the performance requirements required for medical carbon fiber reinforced PEEK. the
较佳地,使用等离子体浸没离子注入技术在聚醚醚酮的表面进行钛离子注入时,使用纯金属钛作为阴极。采用纯金属钛作为阴极注入钛离子,提高聚醚醚酮的生物相容性的同时仍能保持材料的良好的力学性能。 Preferably, when plasma immersion ion implantation technology is used to implant titanium ions on the surface of polyether ether ketone, pure metallic titanium is used as the cathode. Using pure metal titanium as the cathode to inject titanium ions improves the biocompatibility of polyether ether ketone while still maintaining the good mechanical properties of the material. the
较佳地,所述钛离子注入的工艺参数包括:本底真空度为3×10-3~5×10-3Pa,注入电压为15~40kV,注入脉宽为50~600μs,注入脉冲频率为5~9Hz,阴极源触发脉宽为500~2000μs,注入时间为30~180分钟。 Preferably, the process parameters of the titanium ion implantation include: background vacuum degree of 3×10 -3 to 5×10 -3 Pa, implantation voltage of 15 to 40 kV, implantation pulse width of 50 to 600 μs, implantation pulse frequency 5-9Hz, the trigger pulse width of the cathode source is 500-2000μs, and the injection time is 30-180 minutes.
进一步优选地,所述注入脉宽为200~600μs,所述注入时间为60~180分钟。 Further preferably, the injection pulse width is 200-600 μs, and the injection time is 60-180 minutes. the
在一个优选的示例中,所述本底真空度为3.5×10-3Pa,所述注入电压为15kV,所述注入脉冲频率为7Hz,所述注入脉宽为450μs,所述注入时间为90分钟。在又一个优选的示例中,所述本底真空度为3.5×10-3Pa,所述注入电压为30kV,所述注入脉冲频率为7Hz,所述注入脉宽为450μs,所述注入时间为120分钟。 In a preferred example, the background vacuum is 3.5×10 -3 Pa, the injection voltage is 15kV, the injection pulse frequency is 7Hz, the injection pulse width is 450μs, and the injection time is 90 minute. In yet another preferred example, the background vacuum is 3.5×10 -3 Pa, the injection voltage is 30kV, the injection pulse frequency is 7Hz, the injection pulse width is 450μs, and the injection time is 120 minutes.
本发明中,所述的聚醚醚酮为纯聚醚醚酮材料或碳纤维增强聚醚醚酮材料。 In the present invention, the polyether ether ketone is a pure polyether ether ketone material or a carbon fiber reinforced polyether ether ketone material. the
当所述的聚醚醚酮为纯聚醚醚酮材料,钛离子注入纯聚醚醚酮表面以使其表面具有纳米颗粒和纳米薄膜。钛元素和纳米结构的引入可以改善纯聚醚醚酮的抗菌性和生物相容性。 When the polyetheretherketone is a pure polyetheretherketone material, titanium ions are implanted on the surface of the pure polyetheretherketone to have nano particles and nano films on the surface. The introduction of titanium elements and nanostructures can improve the antibacterial properties and biocompatibility of pure PEEK. the
当所述的聚醚醚酮为碳纤维增强聚醚醚酮材料,钛离子注入碳纤维增强聚醚醚酮表面以使其表面具有多孔和纳米颗粒的多级结构。钛元素和纳米结构的引入显著地改善了碳纤维增强聚醚醚酮的抗菌性和生物相容性。 When the polyether ether ketone is a carbon fiber reinforced polyether ether ketone material, titanium ions are implanted into the surface of the carbon fiber reinforced polyether ether ketone so that the surface has a porous and nano-particle multi-level structure. The introduction of titanium element and nanostructure significantly improved the antibacterial and biocompatibility of carbon fiber reinforced polyetheretherketone. the
与现有技术相比,本发明具有如下有益效果: Compared with prior art, the present invention has following beneficial effect:
经过本发明改性方法处理得到的聚醚醚酮材料,具有一定的抗菌性,同时生物相容性有较大 程度的提高。细胞增殖实验结果证实,经过本发明改性方法处理得到的聚醚醚酮材料具有较好的细胞相容性,MC3T3细胞在改性表面增殖明显高于未改性表面,能满足医用聚醚醚酮材料所需的生物相容性要求。 The polyether ether ketone material obtained through the modification method of the present invention has certain antibacterial properties, and at the same time, the biocompatibility is greatly improved. The results of the cell proliferation experiment confirmed that the polyether ether ketone material obtained by the modification method of the present invention has better cytocompatibility, and the proliferation of MC3T3 cells on the modified surface is significantly higher than that on the unmodified surface, which can meet the requirements of medical polyetherether ether. Biocompatibility requirements required for ketone materials. the
附图说明 Description of drawings
图1是经实施例1改性处理得到的碳纤维增强聚醚醚酮与未改性碳纤维增强聚醚醚酮表面的扫描电镜形貌对照图,图中:(a)和(b)为未改性碳纤维增强聚醚醚酮,(c)和(d)为改性处理得到的碳纤维增强聚醚醚酮; Fig. 1 is a scanning electron microscope topography comparison diagram of the surface of carbon fiber reinforced polyetheretherketone and unmodified carbon fiber reinforced polyether ether ketone obtained through the modification treatment of Example 1, in the figure: (a) and (b) are unmodified Carbon fiber reinforced polyether ether ketone, (c) and (d) are carbon fiber reinforced polyether ether ketone obtained by modification treatment;
图2是经实施例1改性处理得到的碳纤维增强聚醚醚酮与未改性碳纤维增强聚醚醚酮断面的扫描电镜形貌对照图,图中:(a)和(c)为未改性碳纤维增强聚醚醚酮,(b)和(d)为改性处理得到的碳纤维增强聚醚醚酮; Fig. 2 is a scanning electron microscope morphology comparison diagram of the carbon fiber reinforced polyether ether ketone obtained through the modification treatment of Example 1 and the unmodified carbon fiber reinforced polyether ether ketone section, in the figure: (a) and (c) are unmodified Carbon fiber reinforced polyether ether ketone, (b) and (d) are carbon fiber reinforced polyether ether ketone obtained by modification treatment;
图3是经实施例1改性处理得到的碳纤维增强聚醚醚酮表面XPS全谱谱图,图中:横坐标表示结合能,纵坐标表示峰强; Fig. 3 is the XPS full spectrum spectrogram of the surface of carbon fiber reinforced polyether ether ketone obtained through the modification treatment of Example 1, in the figure: the abscissa represents the binding energy, and the ordinate represents the peak intensity;
图4是经实施例1改性处理得到的碳纤维增强聚醚醚酮表面钛元素的XPS高分辨谱谱图,图中:横坐标表示结合能,纵坐标表示峰强; Fig. 4 is the XPS high-resolution spectrogram of the titanium element on the surface of carbon fiber reinforced polyether ether ketone obtained through the modification treatment of Example 1, in the figure: the abscissa represents the binding energy, and the ordinate represents the peak intensity;
图5是经实施例1改性处理得到的碳纤维增强聚醚醚酮表面元素深度分布谱图,图中:横坐标表示深度,单位为纳米;纵坐标表示原子百分比例; Fig. 5 is the carbon fiber reinforced polyetheretherketone surface element depth distribution spectrogram obtained through the modification treatment of Example 1, in the figure: the abscissa represents the depth, and the unit is nanometer; the ordinate represents the atomic percentage;
图6是经实施例5改性处理得到的纯聚醚醚酮与未改性纯聚醚醚酮表面的扫描电镜形貌对照图,图中:(a)和(b)为未改性纯聚醚醚酮,(c)和(d)为改性处理得到的纯聚醚醚酮; Fig. 6 is a comparison diagram of scanning electron microscope morphology of the surface of pure polyetheretherketone obtained through modification in Example 5 and the surface of unmodified pure polyether ether ketone. In the figure: (a) and (b) are unmodified pure polyetheretherketone Polyether ether ketone, (c) and (d) are pure polyether ether ketone obtained by modification treatment;
图7是经本发明改性处理前后的碳纤维增强聚醚醚酮抗菌实验结果,图中:(a)和(b)表示处理前样品,(c)和(d)表示Ti-120样品,Ti-120表示30kV偏压下注入钛离子120min的样品; Fig. 7 is the antibacterial experiment result of carbon fiber reinforced polyetheretherketone before and after the modified treatment of the present invention, among the figure: (a) and (b) represent the sample before treatment, (c) and (d) represent Ti-120 sample, Ti -120 indicates the sample implanted with titanium ions for 120min under 30kV bias;
图8是经本发明改性处理前后的碳纤维增强聚醚醚酮表面培养MC3T3成骨细胞形貌扫描电镜图,图中:(a-i)表示处理前样品(i=1、4和7),(b-i)表示Ti-120样品(i=1、4和7),Ti-120表示30kV偏压下注入钛离子120min的样品; Fig. 8 is a scanning electron microscope image of MC3T3 osteoblasts cultured on the surface of carbon fiber reinforced polyetheretherketone before and after the modified treatment of the present invention, in the figure: (a-i) represents the sample before treatment (i=1, 4 and 7), ( b-i) indicates Ti-120 samples (i=1, 4 and 7), and Ti-120 indicates samples implanted with titanium ions for 120min under 30kV bias;
图9是经本发明改性处理前后的碳纤维增强聚醚醚酮表面培养MC3T3成骨细胞的增殖实验结果,图中:对照表示处理前的碳纤维增强聚醚醚酮材料,Ti-120表示30kV偏压下注入钛离子120min的样品。 Fig. 9 is the result of the proliferation experiment of MC3T3 osteoblasts cultured on the surface of carbon fiber reinforced polyether ether ketone before and after the modified treatment of the present invention. A sample that was implanted with titanium ions for 120 minutes under pressure. the
具体实施方式 Detailed ways
以下结合下述实施方式进一步说明本发明,应理解,下述实施方式仅用于说明本发明,而非限制本发明。 The present invention will be further described below in conjunction with the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, not to limit the present invention. the
本发明公开了一种在医用聚醚醚酮及其衍生复合材料表面进行改性的方法,该方法 创新性地提出采用等离子体浸没离子注入技术在纯聚醚醚酮和碳纤维增强聚醚醚酮表面进行钛离子注入,解决现有医用聚醚醚酮材料植入人体后存在的生物相容性不佳和骨组织长入难等问题。 The invention discloses a method for modifying the surface of medical polyether ether ketone and its derivative composite materials. The surface is implanted with titanium ions to solve the problems of poor biocompatibility and difficulty in bone tissue growth after the existing medical polyether ether ketone material is implanted into the human body. the
为解决上述技术问题,本发明采用的技术方案如下: In order to solve the problems of the technologies described above, the technical scheme adopted in the present invention is as follows:
一种医用聚醚醚酮材料的表面改性方法,包括:使用钛离子注入法对纯聚醚醚酮及碳纤维增强聚醚醚酮材料进行表面改性,在纯聚醚醚酮表面形成纳米颗粒结构,在碳纤维增强聚醚醚酮表面构建多孔和纳米颗粒共存结构。 A method for surface modification of medical polyether ether ketone materials, comprising: using a titanium ion implantation method to modify the surface of pure polyetheretherketone and carbon fiber reinforced polyether ether ketone materials, and forming nanoparticles on the surface of pure polyetheretherketone structure, constructing a porous and nanoparticle coexistence structure on the surface of carbon fiber reinforced polyether ether ketone. the
作为优选方案,采用等离子体浸没离子注入(PIII)技术在医用聚醚醚酮材料表面注入钛离子。 As a preferred solution, plasma immersion ion implantation (PIII) technology is used to implant titanium ions on the surface of the medical polyether ether ketone material. the
优选地,采用等离子体浸没离子注入技术在医用聚醚醚酮材料表面注入钛离子时,优选纯钛作为阴极。 Preferably, when plasma immersion ion implantation technology is used to implant titanium ions on the surface of the medical polyether ether ketone material, pure titanium is preferably used as the cathode. the
所述钛离子注入的工艺参数包括:本底真空度为3×10-3~5×10-3Pa,注入电压为15~40kV,注入脉宽为50~600μs(优选200~600μs),注入脉冲频率为5~9Hz,阴极源触发脉宽为500~2000μs,注入时间为30~180分钟(优选60~180分钟)。 The process parameters of the titanium ion implantation include: the background vacuum degree is 3×10 -3 to 5×10 -3 Pa, the implantation voltage is 15 to 40 kV, the implantation pulse width is 50 to 600 μs (preferably 200 to 600 μs), the implantation The pulse frequency is 5-9 Hz, the trigger pulse width of the cathode source is 500-2000 μs, and the injection time is 30-180 minutes (preferably 60-180 minutes).
在一个尤其优选的示例中,采用等离子体浸没离子注入技术在医用聚醚醚酮材料表面注入钛离子的工艺参数优选为:本底真空度为3.5×10-3Pa,注入电压为15kV,注入脉宽为450μs,注入脉冲频率为7Hz,阴极源触发脉宽为500μs,注入时间为90分钟。 In a particularly preferred example, the process parameters for implanting titanium ions on the surface of medical polyetheretherketone materials by using plasma immersion ion implantation technology are preferably: the background vacuum is 3.5×10 -3 Pa, the implantation voltage is 15kV, and the implantation The pulse width is 450 μs, the injection pulse frequency is 7 Hz, the cathode source trigger pulse width is 500 μs, and the injection time is 90 minutes.
在又一个尤其优选的示例中,采用等离子体浸没离子注入技术在医用聚醚醚酮材料表面注入钛离子的工艺参数优选为:本底真空度为3.5×10-3Pa,注入电压为30kV,注入脉宽为450μs,注入脉冲频率为7Hz,阴极源触发脉宽为500μs,注入时间为120分钟。 In yet another particularly preferred example, the process parameters for implanting titanium ions on the surface of medical polyether ether ketone materials by using plasma immersion ion implantation technology are preferably: the background vacuum degree is 3.5×10 -3 Pa, the implantation voltage is 30kV, The injection pulse width is 450 μs, the injection pulse frequency is 7 Hz, the cathode source trigger pulse width is 500 μs, and the injection time is 120 minutes.
上述的聚醚醚酮材料为纯聚醚醚酮材料或碳纤维增强聚醚醚酮材料。 The above polyetheretherketone material is a pure polyetheretherketone material or a carbon fiber reinforced polyetheretherketone material. the
经过本发明改性方法处理得到的聚醚醚酮材料,具有一定的抗菌性,同时生物相容性有较大程度的提高。细胞增殖实验结果证实,经过本发明改性方法处理得到的聚醚醚酮材料具有较好的细胞相容性,MC3T3细胞在改性表面增殖明显高于未改性表面,能满足医用聚醚醚酮材料所需的生物相容性要求。例如,经过本发明表面改性处理得到的纯聚醚醚酮表面分布有纳米颗粒和纳米薄膜,钛元素和纳米结构的引入可以改善纯聚醚醚酮的抗菌性和生物相容性。参见图6,1其示出改性处理得到的纯聚醚醚酮与未改性纯聚醚醚酮表面的扫描电镜形貌对照图,图中:(a)和(b)为未改性纯聚醚醚酮,(c)和(d)为改性处理得到的纯聚醚醚酮,由图6可见:经本实施例改性处理得到的纯聚醚醚酮表面具有明显的纳米颗粒结构,颗粒粒径约为10nm左右,且纳米颗粒分布比较均匀。 The polyether ether ketone material obtained through the modification method of the invention has certain antibacterial properties, and at the same time, the biocompatibility is greatly improved. The results of the cell proliferation experiment confirmed that the polyether ether ketone material obtained by the modification method of the present invention has better cytocompatibility, and the proliferation of MC3T3 cells on the modified surface is significantly higher than that on the unmodified surface, which can meet the requirements of medical polyetherether ether. Biocompatibility requirements required for ketone materials. For example, nanoparticles and nanofilms are distributed on the surface of pure polyetheretherketone obtained through the surface modification treatment of the present invention, and the introduction of titanium elements and nanostructures can improve the antibacterial properties and biocompatibility of pure polyetheretherketone. Refer to Fig. 6, 1 which shows the comparison diagram of scanning electron microscope morphology of the surface of pure polyether ether ketone obtained by modification treatment and unmodified pure polyether ether ketone, in the figure: (a) and (b) are unmodified Pure polyether ether ketone, (c) and (d) are pure polyether ether ketone obtained by modification treatment, as can be seen from Figure 6: the surface of pure polyether ether ketone obtained by modification treatment in this example has obvious nanoparticles structure, the particle size is about 10nm, and the distribution of nanoparticles is relatively uniform. the
又,例如,经过本发明表面改性处理得到的碳纤维增强聚醚醚酮表面分布有100nm左右孔结构,孔结构中分布有粒径大小为10nm左右的纳米颗粒。钛元素和纳米结构的引入显著地改善了碳纤维增强聚醚醚酮的抗菌性和生物相容性。图1和图2分别示出经实施例1改性处理得到的碳纤维增强聚醚醚酮与未改性碳纤维增强聚醚醚酮表面的扫描电镜形貌对照图和断面的扫描电镜形貌对照图,图1中,(a)和(b)为未改性碳纤维增强聚醚醚酮,(c)和(d)为改性处理得到的碳纤维增强聚醚醚酮,图2中,(a)和(c)为未改性碳纤维增强聚醚醚酮,(b)和(d)为改性处理得到的碳纤维增强聚醚醚酮。由图1和图2可见:经本实施例改性处理得到的碳纤维增强聚醚醚酮表面具有明显的孔结构,孔结构深度约为700nm-800nm,孔结构中分布有粒径为10nm左右的氧化钛纳米颗粒,且纳米颗粒分布比较均匀。图3是经本实施例改性处理得到的碳纤维增强聚醚醚酮材料表面XPS全谱谱图。图4是经实施例1改性处理得到的碳纤维增强聚醚醚酮表面钛元素的XPS高分辨谱谱图。图5是经实施例1改性处理得到的碳纤维增强聚醚醚酮表面元素深度分布图。由图3、图4和图5可知:使用等离子体浸没离子注入技术可以将钛元素引入至聚醚醚酮表面,表面钛元素以氧化钛形式存在,钛元素在分布较大深度范围,且元素含量随深度增加而降低。图7是经实施例1改性处理得到的碳纤维增强聚醚醚酮与未改性样细菌形貌图。由图7可知:改性样品表面细菌较少,且细菌失去原有的饱满圆润形态,具有不同程度的变形扭曲,表明改性材料对金黄色葡萄球菌具有一定抗菌性。图8是经本发明改性处理前后的碳纤维增强聚醚醚酮表面MC3T3成骨细胞形貌扫描电镜图,图中:(a-i)表示处理前样品(i=1、4和7),(b-i)表示Ti-120样品(i=1、4和7)。由图8可知:改性样品细胞伪足伸展更多,形态更为铺展,显示出改性样品具有更好的细胞相容性。图9是经实施例1改性处理得到的碳纤维增强聚醚醚酮与未改性碳纤维增强聚醚醚酮的MC3T3细胞增殖实验统计结果。由图9可见:MC3T3细胞在经上述实施例1改性处理得到的碳纤维增强聚醚醚酮表面增殖情况明显好于未改性碳纤维增强聚醚醚酮,显示出改性样品具有较好的生物相容性。 Also, for example, the carbon fiber reinforced polyether ether ketone obtained through the surface modification treatment of the present invention has a pore structure of about 100 nm distributed on the surface, and nanoparticles with a particle size of about 10 nm are distributed in the pore structure. The introduction of titanium element and nanostructure significantly improved the antibacterial and biocompatibility of carbon fiber reinforced polyetheretherketone. Fig. 1 and Fig. 2 respectively show the comparison diagram of scanning electron microscope morphology of the surface of carbon fiber reinforced polyether ether ketone obtained through the modification treatment of Example 1 and the surface of unmodified carbon fiber reinforced polyetheretherketone and the comparison diagram of scanning electron microscope morphology of the cross section , in Figure 1, (a) and (b) are unmodified carbon fiber reinforced polyetheretherketone, (c) and (d) are carbon fiber reinforced polyetheretherketone obtained by modification treatment, in Figure 2, (a) and (c) are unmodified carbon fiber reinforced polyether ether ketone, (b) and (d) are carbon fiber reinforced polyether ether ketone obtained by modification treatment. It can be seen from Figure 1 and Figure 2 that the surface of the carbon fiber reinforced polyether ether ketone obtained through the modification treatment of this embodiment has an obvious pore structure, the depth of the pore structure is about 700nm-800nm, and particles with a particle size of about 10nm are distributed in the pore structure. Titanium oxide nanoparticles, and the distribution of nanoparticles is relatively uniform. Fig. 3 is an XPS full-spectrum spectrum on the surface of the carbon fiber reinforced polyetheretherketone material obtained through modification treatment in this embodiment. Fig. 4 is an XPS high-resolution spectrum of titanium elements on the surface of carbon fiber reinforced polyetheretherketone obtained through the modification treatment in Example 1. Fig. 5 is a diagram showing the depth distribution of elements on the surface of carbon fiber reinforced polyetheretherketone obtained through the modification treatment in Example 1. From Figure 3, Figure 4 and Figure 5, it can be seen that the titanium element can be introduced to the surface of polyether ether ketone by using plasma immersion ion implantation technology, the surface titanium element exists in the form of titanium oxide, the titanium element is distributed in a large depth range, and the element The content decreases with increasing depth. Fig. 7 is a graph showing the morphology of carbon fiber reinforced polyether ether ketone and unmodified bacteria after modification in Example 1. It can be seen from Figure 7 that there are fewer bacteria on the surface of the modified sample, and the bacteria lose their original plump and round shape, with varying degrees of deformation and distortion, indicating that the modified material has certain antibacterial properties against Staphylococcus aureus. Fig. 8 is a scanning electron microscope image of MC3T3 osteoblasts on the surface of carbon fiber reinforced polyether ether ketone before and after the modification of the present invention, in the figure: (a-i) represents the sample before treatment (i=1, 4 and 7), (b-i ) indicates Ti-120 samples (i=1, 4 and 7). It can be seen from Figure 8 that the pseudopods of the modified samples stretched more, and the morphology was more spread out, showing that the modified samples had better cytocompatibility. Fig. 9 is the statistical result of the MC3T3 cell proliferation experiment of carbon fiber reinforced polyetheretherketone obtained through modification in Example 1 and unmodified carbon fiber reinforced polyetheretherketone. It can be seen from Figure 9 that the proliferation of MC3T3 cells on the surface of carbon fiber-reinforced polyetheretherketone modified in Example 1 is significantly better than that of unmodified carbon fiber-reinforced polyetheretherketone, showing that the modified sample has better biological compatibility. the
下面进一步举例实施例以详细说明本发明。同样应理解,以下实施例只用于对本发明进行进一步说明,而不能理解为对本发明保护范围的限制,本领域的技术人员根据本发明的上述内容作出的一些非本质的改进和调整均属于本发明的保护范围。下述示例具体的工艺参数等也仅是合适范围中的一个示例,即、本领域技术人员可以通过本文的说明做合适的范围内选择,而并非要限定于下文示例的具体数值。 Examples are further given below to describe the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention, and should not be construed as limiting the protection scope of the present invention. Some non-essential improvements and adjustments made by those skilled in the art according to the above contents of the present invention all belong to this invention. protection scope of the invention. The specific process parameters and the like in the following examples are only an example of the appropriate range, that is, those skilled in the art can make a selection within the appropriate range through the description herein, and are not limited to the specific values exemplified below. the
实施例1 Example 1
10mm×10mm×1mm的碳纤维增强聚醚醚酮经过抛光处理后,依次用丙酮和去离子水超声 清洗干净,每次30min,清洗后置于80℃烘箱中烘干并妥善保存。采用等离子体浸没离子注入技术,将钛离子注入碳纤维增强聚醚醚酮基体其具体的工艺参数见表1所示,所获得样品编号Ti-120。 10mm×10mm×1mm carbon fiber reinforced polyether ether ketone is polished, then ultrasonically cleaned with acetone and deionized water, each time for 30min, after cleaning, put it in an oven at 80°C to dry and store it properly. Using plasma immersion ion implantation technology, titanium ions were implanted into carbon fiber reinforced polyether ether ketone matrix. The specific process parameters are shown in Table 1, and the obtained sample number is Ti-120. the
表1钛离子注入参数:
图1是经实施例1改性处理得到的碳纤维增强聚醚醚酮与未改性碳纤维增强聚醚醚酮表面的扫描电镜形貌,图中:(a)和(b)为未改性碳纤维增强聚醚醚酮,(c)和(d)为改性处理得到的碳纤维增强聚醚醚酮。图2是经实施例1改性处理得到的碳纤维增强聚醚醚酮与未改性碳纤维增强聚醚醚酮断面的扫描电镜形貌,图中:(a)和(c)为未改性碳纤维增强聚醚醚酮,(b)和(d)为改性处理得到的碳纤维增强聚醚醚酮。由图1和图2可见:经本实施例改性处理得到的碳纤维增强聚醚醚酮表面具有明显的孔结构,孔结构深度约为700nm-800nm,孔结构中分布有粒径为10nm左右的氧化钛纳米颗粒,且纳米颗粒分布比较均匀。 Figure 1 is the scanning electron microscope morphology of the surface of carbon fiber reinforced polyether ether ketone and unmodified carbon fiber reinforced polyether ether ketone obtained through the modification treatment of Example 1, in the figure: (a) and (b) are unmodified carbon fibers Reinforced polyether ether ketone, (c) and (d) are carbon fiber reinforced polyether ether ketone obtained through modification treatment. Figure 2 is the scanning electron microscope morphology of the carbon fiber reinforced polyether ether ketone and unmodified carbon fiber reinforced polyether ether ketone sections obtained through the modification treatment of Example 1, in the figure: (a) and (c) are unmodified carbon fibers Reinforced polyether ether ketone, (b) and (d) are carbon fiber reinforced polyether ether ketone obtained through modification treatment. It can be seen from Figure 1 and Figure 2 that the surface of the carbon fiber reinforced polyether ether ketone obtained through the modification treatment of this embodiment has an obvious pore structure, the depth of the pore structure is about 700nm-800nm, and particles with a particle size of about 10nm are distributed in the pore structure. Titanium oxide nanoparticles, and the distribution of nanoparticles is relatively uniform. the
图3是经本实施例改性处理得到的碳纤维增强聚醚醚酮材料表面XPS全谱谱图。图4是经实施例1改性处理得到的碳纤维增强聚醚醚酮表面钛元素的XPS高分辨谱谱图。图5是经实施例1改性处理得到的碳纤维增强聚醚醚酮表面元素深度分布图。由图3、图4和图5可知:使用等离子体浸没离子注入技术可以将钛元素引入至聚醚醚酮表面,表面钛元素以氧化钛形式存在,钛元素在分布较大深度范围,且元素含量随深度增加而降低。 Fig. 3 is an XPS full-spectrum spectrum on the surface of the carbon fiber reinforced polyetheretherketone material obtained through modification treatment in this embodiment. Fig. 4 is an XPS high-resolution spectrum of titanium elements on the surface of carbon fiber reinforced polyetheretherketone obtained through the modification treatment in Example 1. Fig. 5 is a diagram showing the depth distribution of elements on the surface of carbon fiber reinforced polyetheretherketone obtained through the modification treatment in Example 1. From Figure 3, Figure 4 and Figure 5, it can be seen that the titanium element can be introduced to the surface of polyether ether ketone by using plasma immersion ion implantation technology, the surface titanium element exists in the form of titanium oxide, the titanium element is distributed in a large depth range, and the element The content decreases with increasing depth. the
实施例2 Example 2
10mm×10mm×1mm的碳纤维增强聚醚醚酮经抛光处理后,依次用丙酮和去离子水超声清洗干净,每次30min,清洗后置于80℃烘箱中烘干并妥善保存。采用等离子体浸没离子注入技术,将钛离子注入碳纤维增强聚醚醚酮基体,其具体的工艺参数见表2所示: After polishing, the 10mm×10mm×1mm carbon fiber reinforced polyetheretherketone is ultrasonically cleaned with acetone and deionized water, each time for 30min, after cleaning, it is dried in an oven at 80°C and stored properly. Using plasma immersion ion implantation technology, titanium ions were implanted into the carbon fiber reinforced polyether ether ketone matrix. The specific process parameters are shown in Table 2:
表2钛离子注入参数:
实施例3 Example 3
10mm×10mm×1mm的碳纤维增强聚醚醚酮经过抛光处理后,依次用丙酮和去离子水超声清洗干净,每次30min,清洗后置于80℃烘箱中烘干并妥善保存。采用等离子体浸没离子注入技术,将钛离子注入碳纤维增强聚醚醚酮基体,其具体的工艺参数见表3所示: After polishing, the 10mm×10mm×1mm carbon fiber reinforced polyether ether ketone was cleaned ultrasonically with acetone and deionized water in sequence, each time for 30 minutes. After cleaning, it was dried in an oven at 80°C and stored properly. Using plasma immersion ion implantation technology, titanium ions were implanted into the carbon fiber reinforced polyether ether ketone matrix. The specific process parameters are shown in Table 3:
表3钛离子注入参数:
实施例4 Example 4
10mm×10mm×1mm的碳纤维增强聚醚醚酮经过抛光处理后,依次用丙酮和去离子水超声清洗干净,每次30min,清洗后置于80℃烘箱中烘干并妥善保存。采用等离子体浸没离子注入技术,将钛离子注入碳纤维增强聚醚醚酮基体,其具体的工艺参数见表4所示: After polishing, the 10mm×10mm×1mm carbon fiber reinforced polyether ether ketone was cleaned ultrasonically with acetone and deionized water in sequence, each time for 30 minutes. After cleaning, it was dried in an oven at 80°C and stored properly. Using plasma immersion ion implantation technology, titanium ions were implanted into the carbon fiber reinforced polyetheretherketone matrix. The specific process parameters are shown in Table 4:
表4钛离子注入参数:
实施例5 Example 5
10mm×10mm×1mm的纯聚醚醚酮经过抛光处理后,依次用丙酮和去离子水超声清洗干净,每次30min,清洗后置于80℃烘箱中烘干并妥善保存。采用等离子体浸没离子注入技术,将钛离子注入纯聚醚醚酮基体,其具体的工艺参数见表5所示: 10mm×10mm×1mm pure polyether ether ketone is polished, then ultrasonically cleaned with acetone and deionized water in sequence, each time for 30 minutes, after cleaning, it is dried in an oven at 80°C and stored properly. Plasma immersion ion implantation technology was used to implant titanium ions into the pure polyether ether ketone matrix. The specific process parameters are shown in Table 5:
表5钛离子注入参数:
图6是经实施例5改性处理得到的纯聚醚醚酮与未改性纯聚醚醚酮表面的扫描电镜形貌对照图,图中:(a)和(b)为未改性纯聚醚醚酮,(c)和(d)为改性处理得到的纯聚醚醚酮。由图6可见:经本实施例改性处理得到的纯聚醚醚酮表面具有明显的纳米颗粒结构,颗粒粒径约为10nm左右,且纳米颗粒分布比较均匀。 Fig. 6 is a comparison diagram of scanning electron microscope morphology of the surface of pure polyetheretherketone obtained through modification in Example 5 and the surface of unmodified pure polyether ether ketone. In the figure: (a) and (b) are unmodified pure polyetheretherketone Polyether ether ketone, (c) and (d) are pure polyether ether ketone obtained by modification. It can be seen from FIG. 6 that the surface of the pure polyether ether ketone obtained through the modification treatment of this embodiment has an obvious nanoparticle structure, the particle size is about 10 nm, and the distribution of nanoparticles is relatively uniform. the
实施例6 Example 6
选用金黄色葡萄球菌(Staphylococcus aureus),采用抗菌实验评估经上述实施例1改性所得碳纤维增强聚醚醚酮材料的抗菌性,利用扫描电子显微镜观察材料表面细菌形貌。具体步骤如下:(1)将使用75%乙醇灭菌的样品置于培养板中,吸取60μL密度为107cfu/mL的菌液接种于样品表面,保持湿度大于90%,置于36.5℃厌氧恒温箱中培养24h。(2)取出样品,用2%戊二醛在室温下固定24小时,用PBS清洗三遍。(3)用梯度酒精(30%、50%、75%、90%、95%和100%)对已固定的细菌进行脱水处理。(4)将试样依次置于不同配比的酒精和六甲基二硅胺烷(HMDS)的混合溶液(酒精:HMDS=2:1、1:1、1:2和100%HMDS)中进行干燥,处理时间各10min。试样喷金后用SEM观察样品表面的细菌形态。 Staphylococcus aureus was selected to evaluate the antibacterial property of the carbon fiber reinforced polyetheretherketone material modified in the above-mentioned Example 1 by using an antibacterial experiment, and the morphology of bacteria on the surface of the material was observed by scanning electron microscopy. The specific steps are as follows: (1) Place the sample sterilized with 75% ethanol on a culture plate, inoculate 60 μL of bacterial solution with a density of 10 7 cfu/mL on the surface of the sample, keep the humidity above 90%, and place it in a 36.5°C Incubate for 24 h in an oxygen incubator. (2) The samples were taken out, fixed with 2% glutaraldehyde at room temperature for 24 hours, and washed three times with PBS. (3) Dehydrate the fixed bacteria with graded alcohol (30%, 50%, 75%, 90%, 95% and 100%). (4) Place the sample in a mixed solution of alcohol and hexamethyldisilazane (HMDS) in different proportions in turn (alcohol: HMDS=2:1, 1:1, 1:2 and 100% HMDS) Drying is carried out, and the treatment time is 10 minutes each. After the sample was sprayed with gold, the morphology of bacteria on the surface of the sample was observed by SEM.
图7是经上述实施例1改性处理得到的碳纤维增强聚醚醚酮与未改性样细菌形貌图。由图7可知:改性样品表面细菌较少,且细菌失去原有的饱满圆润形态,具有不同程度的变形扭曲,表明改性材料对金黄色葡萄球菌具有一定抗菌性。 Fig. 7 is a graph showing the morphology of carbon fiber reinforced polyether ether ketone and unmodified bacteria obtained through the modification treatment of Example 1 above. It can be seen from Figure 7 that there are fewer bacteria on the surface of the modified sample, and the bacteria lose their original plump and round shape, with varying degrees of deformation and distortion, indicating that the modified material has certain antibacterial properties against Staphylococcus aureus. the
实施例7 Example 7
选用MC3T3成骨细胞,采用体外细胞培养实验评估经上述实施例1改性处理所得碳纤维增强聚醚醚酮材料的细胞相容性。利用SEM观察材料表面细胞形貌,实验步骤如下:(1)将使用75%乙醇灭菌的样品放入24孔培养板中,每孔滴加1mL密度为5×104cell/mL MC3T3细胞悬液。(2)将细胞培养板放入5%CO2饱和湿度的细胞培养箱中36.5℃孵化18h。(3)吸去细胞培养液,用PBS清洗样品表面后,将样品移至新的24孔板内,放入培养箱中继续培养。(4)细胞培养1、4和7天后,取出样品,用2%戊二醛在室温下固定24小时,用PBS清洗三遍。(5)用梯度酒精(30%、50%、75%、90%、95%和100%)对已固定的细胞进行脱水处理。(6)将试样依次置于不同配比的酒精和六甲基二硅胺烷(HMDS)的混合溶液(酒精:HMDS=2:1、1:1、1:2和100%HMDS)中进行干燥,处理时间各10min。试样喷金后用SEM观察样品表面的细胞形态。 MC3T3 osteoblasts were selected, and the cell compatibility of the carbon fiber-reinforced polyetheretherketone material obtained through the modification in the above-mentioned Example 1 was evaluated by in vitro cell culture experiments. Use SEM to observe the cell morphology on the surface of the material. The experimental steps are as follows: (1) Put the sample sterilized with 75% ethanol into a 24-well culture plate, and add 1 mL of MC3T3 cell suspension with a density of 5×10 4 cell/mL to each well. liquid. (2) Place the cell culture plate in a cell culture incubator with 5% CO 2 saturated humidity and incubate at 36.5°C for 18h. (3) Aspirate the cell culture medium, wash the surface of the sample with PBS, transfer the sample to a new 24-well plate, and put it into an incubator to continue culturing. (4) After the cells were cultured for 1, 4 and 7 days, the samples were taken out, fixed with 2% glutaraldehyde at room temperature for 24 hours, and washed three times with PBS. (5) Dehydrate the fixed cells with graded alcohol (30%, 50%, 75%, 90%, 95% and 100%). (6) Place the sample in a mixed solution of alcohol and hexamethyldisilazane (HMDS) in different proportions in turn (alcohol: HMDS=2:1, 1:1, 1:2 and 100% HMDS) Drying is carried out, and the treatment time is 10 minutes each. After the sample was sprayed with gold, the cell morphology on the surface of the sample was observed by SEM.
图8是经本发明改性处理前后的碳纤维增强聚醚醚酮表面MC3T3成骨细胞形貌扫描电镜图,图中:(a-i)表示处理前样品(i=1、4和7),(b-i)表示Ti-120样品(i=1、4和7)。由图8可知:改性样品细胞伪足伸展更多,形态更为铺展,显示出改性样品具有更好的细胞相容性。 Fig. 8 is a scanning electron microscope image of MC3T3 osteoblasts on the surface of carbon fiber reinforced polyether ether ketone before and after the modification of the present invention, in the figure: (a-i) represents the sample before treatment (i=1, 4 and 7), (b-i ) indicates Ti-120 samples (i=1, 4 and 7). It can be seen from Figure 8 that the pseudopods of the modified samples stretched more, and the morphology was more spread out, showing that the modified samples had better cytocompatibility. the
实施例8 Example 8
采用MC3T3细胞体外培养实验评估经上述实施例1改性处理所得碳纤维增强聚醚醚酮材料的细胞相容性。利用AlamarBlueTM(AbD serotec Ltd,UK)试剂盒检测细胞在材料表面的增殖 情况。方法如下:(1)将使用75%乙醇灭菌的样品放入24孔培养板中,每孔滴加1mL密度为5×104cell/mL MC3T3细胞悬液。(2)将细胞培养板放入5%CO2饱和湿度的细胞培养箱中36.5℃孵化18h。(3)吸去细胞培养液,用PBS清洗样品表面后,将样品移至新的24孔板内,放入培养箱中继续培养。(4)细胞培养1、4和7天后,吸去原培养液,加入含有5%AlamarBlueTM染液的新培养液,将培养板置于培养箱中培养4h后,从每孔取出100μL培养液放入96孔板中。(5)利用酶标仪(BIO-TEK,ELX800)测量各孔在570nm和600nm波长下的吸光度值。按照以下公式计算AlamarBlueTM被细胞还原的百分率: The cytocompatibility of the carbon fiber reinforced polyether ether ketone material obtained through the modification treatment of the above-mentioned Example 1 was evaluated by MC3T3 cell culture experiment in vitro. AlamarBlue TM (AbD serotec Ltd, UK) kit was used to detect the proliferation of cells on the material surface. The method is as follows: (1) Put the sample sterilized with 75% ethanol into a 24-well culture plate, and add 1 mL of MC3T3 cell suspension with a density of 5×10 4 cell/mL dropwise to each well. (2) Place the cell culture plate in a cell culture incubator with 5% CO 2 saturated humidity and incubate at 36.5°C for 18h. (3) Aspirate the cell culture medium, wash the surface of the sample with PBS, transfer the sample to a new 24-well plate, and put it into an incubator to continue culturing. (4) After 1, 4 and 7 days of cell culture, suck off the original culture solution, add a new culture solution containing 5% AlamarBlue TM staining solution, place the culture plate in the incubator for 4 hours, and take out 100 μL of the culture solution from each well Place in a 96-well plate. (5) Use a microplate reader (BIO-TEK, ELX800) to measure the absorbance values of each well at wavelengths of 570 nm and 600 nm. Calculate the percentage of AlamarBlue TM reduced by cells according to the following formula:
公式: Formula:
其中:A为吸光度值,A`为阴性对照孔的吸光度值,λ1=570nm,λ2=600nm。 Among them: A is the absorbance value, A` is the absorbance value of the negative control well, λ1=570nm, λ2=600nm. the
图9是经上述实施例1改性处理得到的碳纤维增强聚醚醚酮与未改性碳纤维增强聚醚醚酮的MC3T3细胞增殖实验统计结果。由图9可见:MC3T3细胞在经上述实施例1改性处理得到的碳纤维增强聚醚醚酮表面增殖情况明显好于未改性碳纤维增强聚醚醚酮,显示出改性样品具有较好的生物相容性。 Fig. 9 is the statistical result of the MC3T3 cell proliferation experiment of the carbon fiber reinforced polyetheretherketone obtained through the modification treatment of the above embodiment 1 and the unmodified carbon fiber reinforced polyetheretherketone. It can be seen from Figure 9 that the proliferation of MC3T3 cells on the surface of carbon fiber-reinforced polyetheretherketone modified in Example 1 is significantly better than that of unmodified carbon fiber-reinforced polyetheretherketone, showing that the modified sample has better biological compatibility. the
产业应用性:本发明的方法简单易控,经过本发明改性处理得到的聚醚醚酮材料,其表面可获得不同的纳米结构,生物相容性得到显著提高;并具有潜在的骨诱导生长因子和抗菌药物装载前景,可满足医用聚醚醚酮所需的性能要求。 Industrial Applicability: The method of the present invention is simple and easy to control. The surface of the polyether ether ketone material obtained through the modification treatment of the present invention can obtain different nanostructures, and the biocompatibility is significantly improved; and it has potential osteoinductive growth Factors and antimicrobial drug loading prospects to meet the performance requirements required for medical polyetheretherketone. the
Claims (9)
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201310188259.9A CN103242551B (en) | 2013-05-20 | 2013-05-20 | Method for injecting titanium ions to modify surface of polyether-ether-ketone |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201310188259.9A CN103242551B (en) | 2013-05-20 | 2013-05-20 | Method for injecting titanium ions to modify surface of polyether-ether-ketone |
Publications (2)
| Publication Number | Publication Date |
|---|---|
| CN103242551A true CN103242551A (en) | 2013-08-14 |
| CN103242551B CN103242551B (en) | 2015-02-25 |
Family
ID=48922449
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN201310188259.9A Active CN103242551B (en) | 2013-05-20 | 2013-05-20 | Method for injecting titanium ions to modify surface of polyether-ether-ketone |
Country Status (1)
| Country | Link |
|---|---|
| CN (1) | CN103242551B (en) |
Cited By (8)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN104975267A (en) * | 2014-04-09 | 2015-10-14 | 中国科学院上海硅酸盐研究所 | Method of surface-modifying polyether ether ketone material |
| CN105331946A (en) * | 2015-11-18 | 2016-02-17 | 中国科学院上海硅酸盐研究所 | Method for pouring zirconium ions to improve biological activity of medical polyether-ether-ketone material |
| WO2018220002A1 (en) | 2017-05-30 | 2018-12-06 | Fraunhofer-Gesellschaft zur Förderung der angewandten Forschung eingetragener Verein | Coated substrate having a titanium-containing coating and a modified titanium oxide coating |
| US10195816B2 (en) | 2014-12-01 | 2019-02-05 | Industrial Technology Research Institute | Metal/polymer composite material and method for fabricating the same |
| CN115141404A (en) * | 2022-08-19 | 2022-10-04 | 中南大学湘雅医院 | Dressing and preparation method thereof |
| CN115645607A (en) * | 2022-12-29 | 2023-01-31 | 首都医科大学附属北京口腔医院 | Polyether-ether-ketone material with antibacterial effect and preparation method and application thereof |
| CN116271213A (en) * | 2023-03-13 | 2023-06-23 | 浙江广慈医疗器械有限公司 | A polyetheretherketone-based high-activity biological fuser, preparation method and application thereof |
| CN117959490A (en) * | 2023-05-16 | 2024-05-03 | 杭州明康捷医疗科技有限公司 | A PEEK-based antibacterial orthopedic implant medical device product and preparation method thereof |
Citations (2)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN102330051A (en) * | 2011-09-30 | 2012-01-25 | 中国科学院上海硅酸盐研究所 | Surface modifying method for improving antibacterial property and biological activity of medicinal titanium |
| WO2012167063A1 (en) * | 2011-06-03 | 2012-12-06 | Synthes Usa, Llc | Surgical implant |
-
2013
- 2013-05-20 CN CN201310188259.9A patent/CN103242551B/en active Active
Patent Citations (2)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| WO2012167063A1 (en) * | 2011-06-03 | 2012-12-06 | Synthes Usa, Llc | Surgical implant |
| CN102330051A (en) * | 2011-09-30 | 2012-01-25 | 中国科学院上海硅酸盐研究所 | Surface modifying method for improving antibacterial property and biological activity of medicinal titanium |
Cited By (11)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN104975267A (en) * | 2014-04-09 | 2015-10-14 | 中国科学院上海硅酸盐研究所 | Method of surface-modifying polyether ether ketone material |
| CN104975267B (en) * | 2014-04-09 | 2017-08-11 | 中国科学院上海硅酸盐研究所 | A kind of method that polyetheretherketonematerials materials are carried out with surface modification |
| US10195816B2 (en) | 2014-12-01 | 2019-02-05 | Industrial Technology Research Institute | Metal/polymer composite material and method for fabricating the same |
| CN105331946A (en) * | 2015-11-18 | 2016-02-17 | 中国科学院上海硅酸盐研究所 | Method for pouring zirconium ions to improve biological activity of medical polyether-ether-ketone material |
| WO2018220002A1 (en) | 2017-05-30 | 2018-12-06 | Fraunhofer-Gesellschaft zur Förderung der angewandten Forschung eingetragener Verein | Coated substrate having a titanium-containing coating and a modified titanium oxide coating |
| DE102017111784A1 (en) | 2017-05-30 | 2018-12-06 | Fraunhofer-Gesellschaft zur Förderung der angewandten Forschung e.V. | Coated substrate with titanium-containing coating and modified titanium oxide coating |
| CN115141404A (en) * | 2022-08-19 | 2022-10-04 | 中南大学湘雅医院 | Dressing and preparation method thereof |
| CN115645607A (en) * | 2022-12-29 | 2023-01-31 | 首都医科大学附属北京口腔医院 | Polyether-ether-ketone material with antibacterial effect and preparation method and application thereof |
| CN116271213A (en) * | 2023-03-13 | 2023-06-23 | 浙江广慈医疗器械有限公司 | A polyetheretherketone-based high-activity biological fuser, preparation method and application thereof |
| CN116271213B (en) * | 2023-03-13 | 2023-10-20 | 浙江广慈医疗器械有限公司 | Polyether-ether-ketone-based high-activity biological fusion device, preparation method and application thereof |
| CN117959490A (en) * | 2023-05-16 | 2024-05-03 | 杭州明康捷医疗科技有限公司 | A PEEK-based antibacterial orthopedic implant medical device product and preparation method thereof |
Also Published As
| Publication number | Publication date |
|---|---|
| CN103242551B (en) | 2015-02-25 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| CN103242551B (en) | Method for injecting titanium ions to modify surface of polyether-ether-ketone | |
| Li et al. | Polydopamine-induced nanocomposite Ag/CaP coatings on the surface of titania nanotubes for antibacterial and osteointegration functions | |
| CN107304472B (en) | Medical titanium-based composite coating with both bone repair function and antibacterial properties and preparation method thereof | |
| CN103614699B (en) | Inject the method for tantalum ion to surface of polyether-ether-ketone and the polyetheretherketonematerials materials of modification | |
| Gao et al. | The effects of titania nanotubes with embedded silver oxide nanoparticles on bacteria and osteoblasts | |
| Xu et al. | Polydopamine coatings embedded with silver nanoparticles on nanostructured titania for long-lasting antibacterial effect | |
| CN102330051A (en) | Surface modifying method for improving antibacterial property and biological activity of medicinal titanium | |
| Song et al. | Room-temperature fabrication of a three-dimensional reduced-graphene oxide/polypyrrole/hydroxyapatite composite scaffold for bone tissue engineering | |
| WO2019218754A1 (en) | Material having surface modified by super capacitance, preparation method therefor and application thereof | |
| US10934408B2 (en) | Surface modification method for polyether-ether-ketone material | |
| CN103225067A (en) | Method for modifying polyetheretherketone surface by implanting calcium ions | |
| CN101869725B (en) | Antibacterial bioactivity composite coating comprising nano Ag particles and preparation method | |
| Wang et al. | Long-term antibacterial characteristics and cytocompatibility of titania nanotubes loaded with Au nanoparticles without photocatalytic effects | |
| CN109267137B (en) | A kind of preparation method of medical titanium surface gradient nano-silver | |
| CN107937880B (en) | Method for modifying surface of metal material, product and application thereof | |
| CN105617460A (en) | Method for preparing nontoxic antibacterial coating on surface of medical implant material | |
| CN103881129A (en) | Polyether-ether-ketone material and surface modification method thereof | |
| CN119113218A (en) | A multifunctional bionic coating with both osteogenic induction and antibacterial properties and preparation method thereof | |
| Liu et al. | Cytocompatibility and antibacterial property of N+ ions implanted TiO2 nanotubes | |
| CN112661500B (en) | Biological ceramic bracket with micro-nano structure on surface and preparation method and application thereof | |
| Ding et al. | The Application Progress of Nonthermal Plasma Technology in the Modification of Bone Implant Materials | |
| CN102580149A (en) | Antibiosis coating and preparation method thereof | |
| CN106637121B (en) | A kind of medical titanium metal alkyl materials and its manufacturing method | |
| CN105331946B (en) | A kind of method that zirconium-ion implantation improves medical polyetheretherketonematerials materials bioactivity | |
| CN105132869A (en) | Method for carrying out surface modification on polyether-ether-ketone material and modified polyether-ether-ketone material |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| C06 | Publication | ||
| PB01 | Publication | ||
| C10 | Entry into substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| C14 | Grant of patent or utility model | ||
| GR01 | Patent grant | ||
| TR01 | Transfer of patent right |
Effective date of registration: 20251015 Address after: 315302 Ningbo City, Cixi City, BaiShaLu Street, Wenwei Road 345, Building 1, 3rd Floor, Room 310 (self-declaration) Patentee after: Ningbo Huafu Medical Technology Co.,Ltd. Country or region after: China Address before: 200050 Dingxi Road, Shanghai, Changning District, No. 1295 Patentee before: SHANGHAI INSTITUTE OF CERAMICS, CHINESE ACADEMY OF SCIENCES Country or region before: China |
|
| TR01 | Transfer of patent right |